2011
DOI: 10.2165/11591780-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal Hyperplasia Inhibition Effect of Angiotensin II Type 1 Receptor Blockers in Patients after Coronary Stent Implantation

Abstract: There is no evident benefit with the use of an ARB in terms of inhibition of neointimal hyperplasia in patients after coronary stent implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Though a meta-analysis revealed that use of ARBs cannot inhibit neointimal hyperplasia in patients after coronary stent implantation, the clinical trials that they analyzed did not use telmisartan [65]. Among ARBs, telmisartan has the most potent PPAR- γ -mediated effects, activating the receptor to 25%–30% of the maximum level achieved by full agonists such as pioglitazone and rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Though a meta-analysis revealed that use of ARBs cannot inhibit neointimal hyperplasia in patients after coronary stent implantation, the clinical trials that they analyzed did not use telmisartan [65]. Among ARBs, telmisartan has the most potent PPAR- γ -mediated effects, activating the receptor to 25%–30% of the maximum level achieved by full agonists such as pioglitazone and rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%